Business Intelligence (BI) Implementation - COBIT 4.1 - Firmansyah, Denny (Swiss German University, 2018)
The present paper aims to propose a general procedure to sizing and improve the Information Technology in an organization. The use of information systems has led to the recognition of the importance of quality management in the competitive environment. However, only few companies have taken actions to measure and enhance the quality of information. Hidden costs and poor quality of information may adversely measuring the performance of Business Intelligence systems based on COBIT 4.1 [1]. The value of the study is the ability to use business intelligence for the purpose of implementation and management capability.